RICE PRODUCTION AND ITS DETERMINANTS IN BODOLAND TERRITORIAL REGION (BTR), ASSAM, INDIA - Daimary, Mahar Swrang; Barman, Kaushik; Chanu, A. Ibemcha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Rice production is still the primary source of livelihood of the majority of the population of Bodoland Territorial Region (BTR). The study reveals the production of rice among different types of farmers in the study area. The study found that majority of farmers belong to marginal category but the small farmers have the higher share of total production of rice. Moreover, the Cobb Douglas production function method is used to understand the factors affecting the production in the region and also this study highlights the needs for sustainable agricultural practices to improve the production of rice. The study shows that the compound annual growth rate of area and production has been decreasing over the years but the extensive use of fertilizers has been increasing. This study also revealed the estimated value of the coefficient and related statistics of Cobb-Douglas Production function of rice production. Econometric analysis results revealed that the total area for cultivation and irrigated area contributed significantly to the production of rice in the region.